A bibliometric analysis of team autonomy research - Kristýna Zychová; Tereza Šímová; Martina Fejfarová (Cogent Business & Management, 2023)
Organisations all around the globe are beginning to promote autonomy rather than imposing restrictions. Thus, the use of teams with certain levels of autonomy as an organisational structure has increased in recent years to achieve corporate objectives. The article aims to review the records in the team autonomy research domain. Given the number of possibly interchangeable terms connected to the teams with certain levels of autonomy (self-managing, self-organizing, self-regulating, self-directed or semi-autonomous), a bibliometric analysis was used to obtain data from the Web of Science and Scopus databases. According to annual scientific production and coverage of the terms over time in both databases, bibliometric analysis has shown that the Scopus covers more significantly the total number of records and the time span. The most used term in both databases was "self-managing team". Further, the article provides specific occurrences and frequencies of the terms and descriptions of the records associated with its first occurrences. This article provides the first review of records using bibliometric methods in the team autonomy research domain. It helps to describe the development of the research domain and proposes several bases for future research opportunities.
Keywords: 650; bibliometrics; Scopus; team autonomy; Web of Science